Efficacy of boom systems in limiting runoff on center pivots - Nakawuka, Prossie; Peters, R.T.; Okwany, Romulus O.; Sadeghi, H.S. (2014)
Center pivot and linear move irrigation systems’ design and operation are primarily limited by soil infiltration rates. Boom systems have been suggested to improve infiltration and decrease runoff by reducing the instantaneous water application rate of center pivots and linear move systems. In this research project, we compared runoff from plots irrigated with typical in line sprinklers on a linear move irrigation system with those irrigated with off set boom systems. In line drops consistently generated greater runoff than ‘the boom systems in all of the irrigation events. Differences in runoff between the drop types were significantly different for the second, third, fourth and fifth irrigation events. The runoff differences from in line drops ranged from 3% to 24% greater than the boom systems. Runoff as a percentage of irrigation water applied increased with each irrigation event on both drop types.